2020
DOI: 10.3390/vaccines8030416
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma haematobium Extracellular Vesicle Proteins Confer Protection in a Heterologous Model of Schistosomiasis

Abstract: Helminth parasites release extracellular vesicles which interact with the surrounding host tissues, mediating host–parasite communication and other fundamental processes of parasitism. As such, vesicle proteins present attractive targets for the development of novel intervention strategies to control these parasites and the diseases they cause. Herein, we describe the first proteomic analysis by LC-MS/MS of two types of extracellular vesicles (exosome-like, 120 k pellet vesicles and microvesicle-like, 15 k pel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 97 publications
0
36
0
Order By: Relevance
“…Recently, TSPs were found to be localized in adults S. mansoni and S. hematobium tegument vesicles, not on the surface membrane (Schulte et al 2013 ; Sotillo et al 2015 ), supporting a mechanism of action via release in EVs (i.e. ESP) (Sotillo et al 2016 ; Samoil et al 2018 ; Kifle et al 2020a ; Mekonnen et al 2020 ). The study of Mekonnen et al ( 2020 ) reported that ShTSP-2 conferred a highly significant protection against heterologous challenge ( S. mansoni ) model of infection.…”
Section: Vaccine Candidates In Clinical Trialsmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, TSPs were found to be localized in adults S. mansoni and S. hematobium tegument vesicles, not on the surface membrane (Schulte et al 2013 ; Sotillo et al 2015 ), supporting a mechanism of action via release in EVs (i.e. ESP) (Sotillo et al 2016 ; Samoil et al 2018 ; Kifle et al 2020a ; Mekonnen et al 2020 ). The study of Mekonnen et al ( 2020 ) reported that ShTSP-2 conferred a highly significant protection against heterologous challenge ( S. mansoni ) model of infection.…”
Section: Vaccine Candidates In Clinical Trialsmentioning
confidence: 98%
“…ESP) (Sotillo et al 2016 ; Samoil et al 2018 ; Kifle et al 2020a ; Mekonnen et al 2020 ). The study of Mekonnen et al ( 2020 ) reported that ShTSP-2 conferred a highly significant protection against heterologous challenge ( S. mansoni ) model of infection. However, it is not clear how the ability of anti-TSP antibodies to block vesicle uptake by host target cells explains the potential of TSPs as promising anti-fluke vaccine (Kifle et al 2020b ).…”
Section: Vaccine Candidates In Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mass spectrometry profiling was used to show that over half of the proteins previously identified in the secretome of E. caproni and F. hepatica were associated with extracellular vesicles (EVs) that could be enriched by ultracentrifugation of the culture medium of parasites maintained in vitro [ 34 ]. The EV fraction of F. hepatica , S. mansoni, and S. haematobium adult secretions has been further separated into two populations with distinct protein compositions that pellet at either 15,000× g or 120,000× g by ultracentrifugation (named 15K or 120K EVs) [ 35 , 36 , 37 ]. Characterisation of the surface proteins of F. hepatica EVs was enabled by incubating the vesicles with a membrane-impermeable biotin reagent then performing liquid chromatography-tandem mass spectrometry (LC-MS/MS) on proteins isolated by streptavidin pulldown [ 38 ].…”
Section: A Closer Look At the Adult Fluke Secretomementioning
confidence: 99%
“…Indeed, epidemiological evidence supports the fact that schistosomiasis can protect against allergy in an endemic population ( Medeiros et al., 2003 ; Oliveira et al., 2014 ). Therefore, exploring the schistosomal ‘strategy’ may facilitate the development of novel diagnostic tools ( Meningher et al., 2017 ; Weerakoon et al., 2018 ; Silva-Moraes et al., 2019 ), vaccines ( Sotillo et al., 2016 ; Mekonnen et al., 2020 ) and therapeutic approaches for human schistosomiasis and immune dysregulation ( Siles-Lucas et al., 2015 ; Ayelign et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%